SCHOOL-BASED MANAGEMENT COMMITTEES’ PARTICIPATION IN THE PROVISION OF FUNDS AND SECURITY IN PUBLIC SECONDARY SCHOOLS IN NORTH- WEST ZONE, NIGERIA - Umar, Abubakar Aliyu; KWASHABAWA, BALA BAKWAI (Sokoto Educational Review, 2025)
This study investigated the participation of school-based management committees (SBMCs) in providing funds for public secondary schools in Nigeria's North-West zone. The research used a descriptive survey design. The study population was 45,040, and a sample of 384 participants was selected using a multi-stage sampling technique, following the recommendations of Research Advisor (2006). A researcher-designed questionnaire, titled the “School-based Management Committee Participation Questionnaire” (SBMCPQ), was used to collect data. The SBMCPQ used a modified 4-point Likert scale to measure participants' responses. The instrument's construct and content validity were established by experts in educational administration, planning, and curriculum studies. A Cronbach's alpha reliability index of 0.70 was obtained. Descriptive statistics were used to answer the research questions, and an independent samples t-test was used to test the research hypotheses with the Statistical Package for the Social Sciences (SPSS). The results indicated that SBMCs do participate in providing funds in secondary schools in the North-West zone. The study concluded that school administrators and the Ministry of Education can implement effective monitoring, advocacy, and mobilization strategies to encourage and persuade SBMC members to provide funds, thereby improving the quality of secondary education in the North-West zone of Nigeria. The study recommends that school administrators should collaborate with the Ministry of Education to educate SBMC members through awareness, sensitization, and orientation programs. This would encourage and motivate SBMC members to continue participating in providing funds to improve the quality of secondary education in the North-West Zone, Nigeria. DOI: https://doie.org/10.61132/SER.2025176733